2017
DOI: 10.1016/j.neuron.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Regulation of Synaptic Vesicle Fusion Sites in Central Synapses

Abstract: The number and availability of vesicle release sites at the synaptic active zone (AZ) are critical factors governing neurotransmitter release; yet, these fundamental synaptic parameters have remained undetermined. Moreover, how neural activity regulates the spatiotemporal properties of the release sites within individual central synapses is unknown. Here, we combined a nanoscale imaging approach with advanced image analysis to detect individual vesicle fusion events with ∼27 nm localization precision at single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
171
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(200 citation statements)
references
References 39 publications
29
171
0
Order By: Relevance
“…Consistent with this, a novel imaging approach called pHuse ( pH luorin u ncovering s ites of e xocytosis), using vesicle-resident sensors to map sites of single-vesicle fusion events within individual synapses, demonstrated that action potentials evoked vesicle fusion within a smaller area of the presynaptic bouton than spontaneous release in hippocampal terminals [2**]. Critically, trains of stimuli prompt release from repeatedly used sites [3*]. Thus, release probability (P r ) in a single AZ is spatially heterogeneous.…”
Section: Transsynaptic Alignment Can Control Synaptic Functionmentioning
confidence: 99%
“…Consistent with this, a novel imaging approach called pHuse ( pH luorin u ncovering s ites of e xocytosis), using vesicle-resident sensors to map sites of single-vesicle fusion events within individual synapses, demonstrated that action potentials evoked vesicle fusion within a smaller area of the presynaptic bouton than spontaneous release in hippocampal terminals [2**]. Critically, trains of stimuli prompt release from repeatedly used sites [3*]. Thus, release probability (P r ) in a single AZ is spatially heterogeneous.…”
Section: Transsynaptic Alignment Can Control Synaptic Functionmentioning
confidence: 99%
“…Analysis of putative fusion events at synapses that are fixed with high pressure freezing within ∼10 ms of optogenetic stimulation and analyzed by electron microscopy have revealed a tendency for release towards the center of the active zone (Watanabe et al, 2013). Superresolution localization of individual exocytotic events either aggregated from separate events in multiple synapses (Park et al, 2012) or many events in single synapses (Maschi and Klyachko, 2017; Tang et al, 2016) have shown that individual fusion events are not confined to a single spot, but may be spread out over a subarea of the active zone, perhaps with differences between action potential-mediated and spontaneous fusion events.…”
Section: Relevant Structures and Their Patterning In The Three Synaptmentioning
confidence: 99%
“…Because these estimates are indirect, they may bias the analysis to sites with a relatively high release probability, for example those closer to Ca 2+ channels. Two recent studies have used microscopy to determine the localization of individual vesicle fusion events at hippocampal synapses, with the resolution limited by the size of a synaptic vesicle (Maschi and Klyachko, 2017; Tang et al, 2016). One study subsequently used clustering analysis to determine how many distinct sites were present in a single active zone (Maschi and Klyachko, 2017).…”
Section: Relevant Structures and Their Patterning In The Three Synaptmentioning
confidence: 99%
See 2 more Smart Citations